2017
DOI: 10.2463/mrms.mp.2016-0045
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Silent and Conventional MR Imaging for the Evaluation of Myelination in Children

Abstract: Purpose:Silent magnetic resonance imaging (MRI) scans produce reduced acoustic noise and are considered more gentle for sedated children. The aim of this study was to compare the validity of T1- (T1W) and T2-weighted (T2W) silent sequences for myelination assessment in children with conventional spin-echo sequences.Materials and Methods:A total of 30 children (21 boys, 9 girls; age range: 1–83 months, mean age: 35.5 months, median age: 28.5 months) were examined using both silent and spin-echo sequences. Acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…As a consequence, we may miss some of the relevant BOLD response. There are increasing numbers of research in the field of silent MRI imaging [52, 53], and hopefully, the next generation of MRI scanners will totally be silent. It has been shown that the nature of the task may potentially influence the effects of white noise on cognitive performance [30].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, we may miss some of the relevant BOLD response. There are increasing numbers of research in the field of silent MRI imaging [52, 53], and hopefully, the next generation of MRI scanners will totally be silent. It has been shown that the nature of the task may potentially influence the effects of white noise on cognitive performance [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a method to optimize gradient waveforms was developed and the sequence is called either the "Silent" or "Quiet" sequence. 14,16,22 The technique has been applied to T1WI, T2WI and FLAIR, 14,17 but not yet in other sequences such as DWI.…”
Section: Discussionmentioning
confidence: 99%
“…14 There was one previous study comparing images of the silent T 1 and T 2 weighted image (T1WI, T2WI) PROPELLER technique with that of T1WI spin echo and T2WI fast spin-echo sequences in children in terms of myelination degree. 17 The study compared both the sequences that were acquired by different imaging planes, slice thickness, or matrix, which made hard to match the quality of silent PROPELLER imaging. In addition, the study included patients of a wide age range.…”
Section: Introductionmentioning
confidence: 99%
“…This loud noise often can wake a sedated child (especially neonates and infants), leading to suspended examinations and the need for additional sedatives. Some methods can reduce noise, including the use of diminished gradient slew rate and slow ramps for k ‐space readout . Insulation of the inner bore of the magnet and inserting ear plugs and covering the ears with noise attenuators can reduce the noise experienced by children .…”
Section: Techniques To Minimize Sedation For Pediatric Mri Examinationsmentioning
confidence: 99%
“…Some methods can reduce noise, including the use of diminished gradient slew rate and slow ramps for k-space readout. 29,30 Insulation of the inner bore of the magnet and inserting ear plugs and covering the ears with noise attenuators can reduce the noise experienced by children. 30 However, the effects of those methods are limited.…”
Section: Noise Reductionmentioning
confidence: 99%